Research on optimal configuration of mobile energy storage in distribution networks considering various energy utilization efficiencies - Fu, Dong; Li, Bin; Yin, Liangzhi; Sun, Xuebin; Cui, Hong (Frontiers in Energy Research, 2024)
As renewable energy sources like wind and solar increasingly integrate into the distribution grid, traditional electrical grids encounter unprecedented complexity and instability. This study introduces an innovative method for optimizing Modular Mobile Battery Energy Storage (MMBES) configurations. It investigates five core attributes of energy storage configuration and creates a model that accommodates the uncertainties of extreme scenarios. This approach not only improves the adaptability of energy storage systems but also equips decision-makers with a tool for proactive and adaptable decision-making in complex environments. Empirical research shows that modular mobile energy storage significantly boosts distribution grid performance by effectively addressing the challenges of renewable integration. By fine-tuning decision-makers' cognitive parameters, energy storage configurations better align with subjective preferences, ensuring economic viability and enhancing grid resilience. This study presents a novel perspective and method for configuring energy storage in urban distribution grids amid widespread renewable integration, particularly in capacity-limited areas, offering insights for more flexible and reliable grid operations.